MODELING OF ORE-MAGMATIC SYSTEM OF GOLD DEPOSITS IN EASTERN KAZAKHSTAN - Mizernaya, M.; Orazbekova, G.; Dyachkov, B.; Miroshnicova, A.; Zatserkovnyi, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the results of using system-defined geological modeling for forecasting gold deposits on the territory of the oldest gold mining region in the Republic of Kazakhstan – the West Kalba gold belt (East Kazakhstan). Research is aimed at developing forecast criteria and searches for new ore objects in favorable geological structures. The main attention of the conducted research was focused on a system-defined analysis of geological factors, the interaction of which provides a synergy effect and reveals the patterns of formation of gold ore objects. To solve this problem, the authors made a quantitative assessment of the development sustainability of the ore-generating elements of the system according to S.V. Vasiliev methodology. A quantitative assessment of the stability of individual factors and their interaction made it possible to assess the qualitative state of individual sections and define the natural boundaries of the areas of the corresponding hierarchical level, promising for the search of certain mineral deposits. The specific work was carried out to define the areas promising for the search of deposits based on a quantitative assessment of the individual factors stability. Using geological materials, results of geophysical work, space-geological data, the localization of promising areas within the West Kalba structural-formation zone and the Zhumba ore-magmatic system in East Kazakhstan was done.
Keywords: ore-magmatic system; gold; deposit; assessment of the geological factors stability